ESG Performance and Corporate Tax Aggressiveness: Evidence from Indonesian Listed Firms - Mulya Tantra Gunadi; Putu Agus Ardiana; I Dewa Nyoman Badera; Naniek Noviari (Fakultas Ekonomi dan Bisnis, Universitas Udayana bekerjasama dengan Ikatan Sarjana Ekonomi Cabang Bali, 2025)
This study examines the relationship between Environmental, Social, and Governance (ESG) performance and corporate tax aggressiveness among Indonesian listed firms. Using panel data from non-financial companies that disclosed ESG scores during the 2021–2024 period, this research employs panel regression analysis with the effective tax rate (ETR) as a proxy for tax aggressiveness. The analysis controls for firm-specific characteristics, including firm size, leverage, firm age, liquidity, profitability, market valuation, and board size. Grounded in legitimacy theory, this study investigates whether ESG performance reflects firms’ ethical commitment in tax practices or merely serves as symbolic compliance. The empirical findings indicate that ESG performance is positively associated with ETR, suggesting that firms with higher ESG scores tend to exhibit lower levels of tax aggressiveness. In contrast, profitability is found to be a significant driver of tax aggressiveness. These results provide evidence that ESG performance is relevant in shaping corporate tax behavior and offer insights into the effectiveness of mandatory sustainability reporting in Indonesia. The study contributes to the literature on ESG and taxation in emerging markets.